2003
DOI: 10.1093/nar/gkg766
|View full text |Cite
|
Sign up to set email alerts
|

RNA structure of trinucleotide repeats associated with human neurological diseases

Abstract: The tandem repeats of trinucleotide sequences are present in many human genes and their expansion in specific genes causes a number of hereditary neurological disorders. The normal function of triplet repeats in transcripts is barely known and the role of expanded RNA repeats in the pathogenesis of Triplet Repeat Expansion Diseases needs to be more fully elucidated. Here we have described the structures formed by transcripts composed of AAG, CAG, CCG, CGG and CUG repeats, which were determined by chemical and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
229
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 203 publications
(242 citation statements)
references
References 52 publications
13
229
0
Order By: Relevance
“…CAG repeat RNAs fold into secondary hairpin structures [9][10][11][12] . To give an idea of how these hairpins could look like, we performed in silico RNA-structure predictions of CAG repeat stretches with different repeat sizes.…”
Section: Mid1mentioning
confidence: 99%
See 1 more Smart Citation
“…CAG repeat RNAs fold into secondary hairpin structures [9][10][11][12] . To give an idea of how these hairpins could look like, we performed in silico RNA-structure predictions of CAG repeat stretches with different repeat sizes.…”
Section: Mid1mentioning
confidence: 99%
“…CAG sequences form double-stranded RNA structures, the stability of which increases with repeat-numbers [9][10][11] . For example the CAG repeat region of the HTT messenger RNA (mRNA) forms double-stranded hairpin structures 12 .…”
mentioning
confidence: 99%
“…On the other hand, recent studies revealed the importance of the ataxin-1-specific sequence context for the protein function and showed that even the high level expression of an expanded poly-Q tract protein in the nucleus may be insufficient to cause disease (14). In this light the RNA-mediated mechanisms of pathogenesis, similar to those proposed for DM (15) and FXTAS (16 -18) were also considered for polyglutamine diseases (17)(18)(19)(20)(21). According to this mechanism the expanded repeats in transcripts form long stable hairpins, which recruit double-stranded RNA-binding proteins in a repeat length-dependent manner, sequestering them from other transcripts and interfering with their normal functions (22).…”
mentioning
confidence: 98%
“…Among them were all the CNG repeats shown by our bioinformatic analysis to be the most abundant in transcripts [31]. The quasistable hairpin stem structure is composed of the periodically occurring C-G, G-C pairs and N-N mismatches, and the repeats show a tendency to assume several variantive alignments if this process is not suppressed by the presence of a suitable GC clamp [32]. The characteristic feature of hairpins formed by the CNG repeats is that their structure rigidity increases with repeat length.…”
Section: Cng Repeats Form Hairpin Structures In Transcriptsmentioning
confidence: 93%
“…Not only the diseases caused by the repeat expansions in non-coding sequences [42,51] but also the so-called polyglutamine diseases were considered in this context [31,32,52]. We have shown that at least the RNA hairpin structures, which are behind the RNA pathogenesis in myotonic dystrophy have the same architecture also in other TREDs-related transcripts [32,33]. Thus, they have the potential to interact with the specific dsRNA binding proteins.…”
Section: Unified Model Of Rna-mediated Pathogenesis In Tredsmentioning
confidence: 99%